STUDI ETNOGRAFI PENDIDIKAN PADA SMA NEGERI 1 UBUD BALI: KONSEP AJEG BALI (HINDU) BERBASIS IDEOLOGI TRI HITA KARANA - Sukadi, Sukadi (Jurnal Cakrawala Pendidikan, 2016)
This article concerns a research aimed at explaining ideology was ......._A................’....... a state relevant educational programs in the course shaping a generation of modern students still retaining the Balinese character. The research was an educational ethnographical one, llSillg informants selected purposively by means of a snowball sampling technique. The data, collected by making observations interviews, studying compiled documents, and giving tests to students, were analyzed qualitatively. The results of the research indicate that the school above is a school with Hindu nuances and, relevant with its vision, mission, and goal, has developed certain educational programs to participate in making a success of the moral movement in the Balinese society to actualize a Bali remaining Balinese. The movement to remain Balinese was defined by the teachers and students as a moral one made to retain the Balinese people’s characteristic religious and socio-cultural living, preserved on the basis of the implementation of tri hita karana values. Accordingly, the school has developed educational programs empowering students in taking part in actualizing those values at school, not meaning that the school has abandoned the national educational vision, mission, and goal.